Evaluasi Kinerja Bangunan Irigasi untuk Mendukung Keputusan Penanganan pada DI Kepulungan, Tumpang - Muhammad Sholeh; Yurnalisdel Yurnalisdel; Pamela Dinar Rahma (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
This study aims to evaluate the physical and functional performance of the infrastructure in the Kepulungan Irrigation District (DI), Malang Regency, which serves an agricultural area of 89 hectares. The background of this study is based on the trend of declining performance in the irrigation network due to natural factors such as sedimentation, as well as non-technical disturbances such as settlements and illegal tapping, which can reduce water distribution efficiency. The methodology used in this study is a quantitative approach involving a survey to inventory structures and canals through field walks (walkthroughs or transect walks). Performance assessment was conducted based on the Irrigation System Performance Index (IKSI) standards in accordance with Ministry of Public Works and Public Housing Regulation No. 12/PRT/M/2015, which includes an evaluation of the structural integrity of the structures and the operational smoothness of the water gates. The research results indicate that the condition of the infrastructure in the Kepulungan Irrigation District is in a critically poor state. Field findings identified various levels of damage, ranging from cracks in concrete walls and corrosion-induced degradation of water gate components to sediment accumulation that obstructs water flow. Quantitatively, the performance of this irrigation infrastructure reached only 56.624% of the maximum score of 100%, placing the Kepulungan irrigation network in the “Severely Damaged and in Need of Total Repair” category.